Incompatibility of IV Admixture Administration among Hospitalized Patient at Referral Hospital in Banyumas Regional - Erza Genatrika; Wahyu Utaminingrum; Tsabita Maryam Afurisac (Faculty of Pharmacy, Universitas Pancasila, 2026)
Drug administration to inpatients in referral hospitals is generally performed using intravenous (IV) admixtures. IV admixtures can cause incompatibility problems that can affect the stability and bioavailability of the drugs. This study aimed to determine the potential for incompatibility problems in administering IV admixtures to inpatients in referral hospitals in the Banyumas region. This was a descriptive observational study. Data collection was carried out prospectively with the inclusion criteria of non-cytostatic IV admixtures administered to inpatients from March to May 2024. The potential for incompatibility in IV admixtures was determined based on visual observations and pH values ​​carried out in the laboratory. In addition, we analyzed the Handbook of Injectable Drugs. The results of the study showed that 1516 IV admixtures were obtained within 3 months. Of the 1516 IV admixtures, 40 different IV admixtures had different characteristics. The characteristics of IV admixtures obtained at this referral hospital consisted of IV admixtures-small volume parenteral (36%), IV admixtures-large volume parenteral (5%), and reconstitution (59%). The solvents used included water for injection (94.65%), NaCl 0.9%, and RingerLactate (1.39%). Incompatibility occurred in a mixture of Sodium Phenytoin 50 mg/mL with NaCl 0.9% at concentrations as high as 0.264% (4 occurrences out of 1516 IV mixtures), characterized by the formation of crystals after mixing. From this study, it can be concluded that the administration of IV admixtures to inpatients at the Banyumas Referral Hospital has a low potential for incompatibility (0.264%). However, the mixture of sodium phenytoin with 0.9% NaCl has been proven to cause crystal formation due to a decrease in pH, thus requiring special attention in the practice of mixing intravenous drugs.